Dynamic Evolution of Mung Bean Protein in Alkaline Solutions: Unravelling Vicilin Function Through Molecular Simulation - Afsaneh Taheri; Fatin Natasha Binte Abdul Halim; Juan Du (Food Frontiers)
ABSTRACT This study explored the effects of pH‐shifting over 0, 10, 20, and 30 min on the physicochemical characteristics of mung bean protein (MBP) isolates, identified as MBP0, MBP10, MBP20, and MBP30. The conformational features of vicilin‐type (8S), the primary component of MBP, were studied using molecular dynamics simulations. Our findings revealed the time‐dependent nature of pH‐shifting on protein flexibility, which caused changes in surface charges of MBP from 0 to 30 min. An increase in particle size, solubility, and more uniform distribution among all pH‐shifted samples were observed due to swelling. Smoother and flakier structures in pH‐shifted proteins were detected by scanning electron microscope. Molecular simulations at pH 12.0 revealed enhanced stability of vicilin with greater fluctuation of hydrophilic residues and increased flexibility, which correlated to the experimental results, highlighting vicilin's pivotal role in the flexibility and solubility of MBP during pH changes.